Nitrogen fertilization associated with cold storage and its impacts on the maintenance of peach quality - Caroline Farias Barreto; Renan Navroski; Letícia Vanni Ferreira; Jorge Atílio Benati; Marcelo Barbosa Malgarim; Luis Eduardo Correa Antunes (Bioscience Journal, 2020)
Nitrogen, which is considered the most important nutrient for peach trees, may interfere in both quantitative production characteristics and quality of fruits. This study aimed at evaluating the effect of the combination of doses of N fertilization and different periods of cold storage on physico-chemical and phytochemical characteristics of peaches in post-harvest. The experiment had a randomized complete block design in a 4x3 factorial scheme, i. e., four doses of fertilization (0, 60, 120 and 180 Kg N ha-1) and three periods of storage (on the harvest day, on both the 15th and the 30th storage days at 1±1ºC, each followed by a day of simulated commercialization at 20±1ºC). The following aspects were evaluated in fruits yielded by peach trees of the genotype Cascata 1067: fruit color, soluble solid content, titratable acidity, pulp firmness, mass loss, total phenolic compounds and antioxidant activity. Different periods of cold storage and doses of N fertilization were found to affect epidermis luminosity, pulp firmness and titratable acidity of fruits. Peaches may be stored at low temperatures for 15+1 days. After that, loss of fruit firmness increases. N fertilization affects neither the soluble solid content nor the epidermis color of peaches, but both parameters are influenced by storage. Values of phenolic compounds and antioxidant activity decrease when there is N increment in the soil and when longer storage is carried out. Results suggest that peach composition may be affected by cultural practices, such as N fertilization, in harvest and after storage.